"What is to be sustained?": Perpetuating systemic injustices through sustainable fashion. Issue 1 (9th December 2022) - von Busch, Otto
Abstract: There seems to be a consensus across both the fashion system and academia that "fast fashion" has a problem with sustainability. An increase in consumption of cheap and accessible clothing is behind the rise in extraction and pollution across the world seems obvious, and often the solutions offered span from material and technical solutions to awareness-raising and ethical education of consumers. But most of these interventions either implicitly or explicitly push blame on the consumers of cheap goods. It is "they" who consume too much, the consumers of cheap garments. While goods and behaviors readily available to the upper strata of society are deemed sustainable, it is the aspirational consumption of less affluent consumers that needs to be rectified. This article examines how the general discourse on sustainable fashion strikes unevenly at the lower rungs of social hierarchies, amplifying differences in privilege and wealth while also moralizing, preaching down to, and denigrating the desires of the poor. Using Felix Guattari's framework of the three ecologies, the discussion examines some familiar tropes in sustainability discourse, focusing on three lines: the emphasis on industrial and technological solutionism, the undermining of democratic principles, and the emotional besmirching of aspirations. These three tendencies add up to a contemporary equivalent of sumptuary laws aiming to hold back the social mobility and lowly desires of the masses. While this may not be the intent of the promoters of sustainable fashion, a thoughtless and single-minded critique of fast fashion impacts the dissemination of agency and blame across the definitions of sustainability. The article calls for practitioners to examine the premises of sustainable fashion more closely. Any serious discussion around fashion must start with the question: What is to be sustained?